2019
DOI: 10.1515/mammalia-2019-0101
|View full text |Cite
|
Sign up to set email alerts
|

Fitness of the pestiferous small rodent Mastomys natalensis in an agroecosystem in Mayuge district, Lake Victoria Crescent, Uganda

Abstract: A 2.5-year study was conducted to understand the fitness of Mastomys natalensis in an agroecosystem in relationship with environmental predictors. The study was conducted in Mayuge district, in the Lake Victoria Crescent zone in Eastern Uganda. Fitness was measured in terms of survival, maturation and capture probability and estimated using multi-event capture-recapture models. Survival rates were higher after high rainfall in the previous month and increased with increasing population density of the animals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…The finding of the current study is consistent with Mayamba et al. (2019) who reported that habitat did not affect maturation of M. natalensis in Uganda; the animals had continuous access to food resources and in no way was their normal growth and development impeded. Another best supported model showed maturation rate of females to be lower compared with males which may be due to response to pre‐ or postnatal stress or secretion of puberty‐delaying pheromones in females (Oli & Dobson, 1999).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The finding of the current study is consistent with Mayamba et al. (2019) who reported that habitat did not affect maturation of M. natalensis in Uganda; the animals had continuous access to food resources and in no way was their normal growth and development impeded. Another best supported model showed maturation rate of females to be lower compared with males which may be due to response to pre‐ or postnatal stress or secretion of puberty‐delaying pheromones in females (Oli & Dobson, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Survival and maturation probabilities were modeled in subsequent steps which reduced the amount of models that we needed to run. We first modeled survival after which we modeled maturation (Mariën et al., 2018; Mayamba et al., 2019; Sluydts et al., 2007). Models were ranked using the sample size corrected Akaike's information criterion (AIC; Burnham & Anderson, 2004), where the model with the lowest AIC value was the best fit for the data and selected as starting point for the next modeling step.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a higher number of reproductive individuals and juveniles following the long rainy season in our study are likely associated with vegetation availability driven by rainfall. Generally, the proximate factor leading to the onset of reproduction is access to growing vegetation, which is similar to what many studies have found for other rodent species (Mayamba et al, 2019;Meheretu et al, 2015;Mulungu et al, 2013). On the other way, the lower proportion of reproductively active females and newborns in the dense forest sites may be attributed to the lower availability of food and ground cover due to forest canopy, which allowed animals to migrate in search of food and or left them exposed to direct and indirect effects of predation.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, altitude and mosaic landscape type (swamp, near the river, position to sunlight) are known to influence rodent population size (Richard et al, 2022), but their relative contributions and effects may vary among species. Most studies on African rodent demographic aspects have focused on pest species (Mayamba et al, 2019; Meheretu et al, 2015; Mulungu et al, 2013), while ecology studies on non‐pest montane species, including M. delectorum , are scarce. The aim of the study was therefore to determine the breeding patterns and demographic aspects of M. delectorum which are vital factors in understanding the conservation status of a species (IUCN, 2001).…”
Section: Introductionmentioning
confidence: 99%